2020
DOI: 10.37256/est.132020487
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Thermal Performance Characteristics of an Electrical Power Transformer

Abstract: A 3D numerical simulation was conducted to test the effects of the geometrical and operational parameters on the cooling performance of a three-phase electrical distribution transformer (250 kVA oil natural air natural (ONAN)). The geometric parameters include the shape of the transformer (rectangular, circular, and hexagonal), fins shape (rectangular, semicircular, and trapezoidal) as well it arrangement (asymmetric fin heights and perforated fins). Both of oil temperature and thermal load have been used as b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The average oil temperature for Design C was recorded as 331 K. I note that design D achieves an average temperature of 327 K. This indicates that cooling is significant compared to the traditional design. This is attributed to two factors: First, the fin design allowed for increased surface area for heat transfer in the upper hottest region of the transformer, which is in line with the recommendations of the researcher Azbar et al, [27]. Second, large ventilation channels that conform to the shape of the fin helps keep the fin base away from the hot transformer body.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The average oil temperature for Design C was recorded as 331 K. I note that design D achieves an average temperature of 327 K. This indicates that cooling is significant compared to the traditional design. This is attributed to two factors: First, the fin design allowed for increased surface area for heat transfer in the upper hottest region of the transformer, which is in line with the recommendations of the researcher Azbar et al, [27]. Second, large ventilation channels that conform to the shape of the fin helps keep the fin base away from the hot transformer body.…”
Section: Resultssupporting
confidence: 68%
“…They also found that mild steel has a good ability to transfer heat through the fins surrounding the transformer body. Azbar et al, [27] conducted 3D numerical modelling to test the effects of transformer shape and fins on the cooling performance of ONAN type electrical power distribution transformer. The results showed that the best heat dissipation performance and a significant 12% reduction in oil temperature compared to the conventional transformer were obtained when using the transformer with a perforated trapezoidal fin, hexagonal shape.…”
Section: Introductionmentioning
confidence: 99%
“…Other losses in the coil cause insulation damage and an increase in temperature in the transformer, which results in a decrease in efficiency, performance, and capacity (it is necessary to reduce the maximum load or derating to prevent the overheat) [9]. [10] found that harmonic pollution increases losses, so it is necessary to improve power quality by reducing non-linear loads. As a comparison, THD for linear loads does not experience distortion (THD=4.0 %), while for non-linear loads experiences substantial distortion (THD=26 % for inductive loads and THD 75 % for capacitive loads).…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Simulations demonstrated that these modifications enhance the heat transfer coefficient and the cooling capacity of the radiator. Azbar et al [13] conducted a study. A 3D numerical simulation was conducted to investigate the impact of geometrical and operational parameters on the cooling of three-phase power transmission transformers.…”
Section: Introductionmentioning
confidence: 99%